2008
DOI: 10.1038/clpt.2008.132
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 Induction by Rifampicin in Healthy Subjects: Determination Using the Karolinska Cocktail and the Endogenous CYP3A4 Marker 4β-Hydroxycholesterol

Abstract: The Karolinska cocktail, comprising caffeine, losartan, omeprazole, and quinine, was given before and after administration of rifampicin (20, 100, or 500 mg daily) to measure induction of cytochrome P450 (P450) enzymes. Rifampicin was given for 14 days to eight healthy subjects (all of whom possessed at least one wild-type CYP2C9 and one wild-type CYP2C19 gene) in each dose group. 4beta-hydroxycholesterol was assessed as an endogenous marker of CYP3A4 induction. A fourfold induction of CYP3A4 was seen at the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(152 citation statements)
references
References 33 publications
16
129
0
Order By: Relevance
“…29 We reported previously a poor dose-response relationship in the formation of omeprazole sulfone whereas the 4b-hydroxycholesterol concentration steadily increased with increasing doses of rifampicine, a strong inducer of CYP3A, in healthy volunteers. 30 These observations reinforce the notion that 4b-hydroxycholesterol concentration and the 4b-hydroxycholesterol/cholesterol ratio are better markers than omeprazole/omeprazole sulfone ratio to determine total CYP3A activity.…”
Section: Cyp3a Markersupporting
confidence: 77%
See 1 more Smart Citation
“…29 We reported previously a poor dose-response relationship in the formation of omeprazole sulfone whereas the 4b-hydroxycholesterol concentration steadily increased with increasing doses of rifampicine, a strong inducer of CYP3A, in healthy volunteers. 30 These observations reinforce the notion that 4b-hydroxycholesterol concentration and the 4b-hydroxycholesterol/cholesterol ratio are better markers than omeprazole/omeprazole sulfone ratio to determine total CYP3A activity.…”
Section: Cyp3a Markersupporting
confidence: 77%
“…8 Its plasma concentration increases in subjects treated with known CYP3A4 inducers such as carbamazepine, phenytoin, phenobarbital, rifampicin, ursodeoxycholic acid and efavirenz. 8,[30][31][32][33][34][35] It was also shown that inhibitors of CYP3A4, ritonavir and itraconazol, reduce the plasma level of 4b-hydroxycholesterol. 35,36 However, recently, TomalikScharte et al 37 reported a weak correlation between cholesterol-and midazolam-based CYP3A metrics and hence questioned the validity of 4b-hydroxycholesterol as a CYP3A biomarker.…”
Section: Cyp3a Markermentioning
confidence: 99%
“…For the following calculation, the half-life of CYP3A4 and CC were assumed to be 72 h and 11.1, respectively. Then, we checked whether the R in vivo values could be predicted for different doses of rifampicin by using the above parameter values (Kanebratt et al, 2008). The reported R in vivo values after the administration of 20, 100, and 500 mg dmd.aspetjournals.org of rifampicin daily for 14 days were 1.5, 2.5, and 4.0, respectively, whereas the R predict values were 1.2, 1.9, and 3.5 (Table 7).…”
Section: Resultsmentioning
confidence: 99%
“…Ulf presented an overview from his 20+ years of research on 4β-HC and some of the oxysterols' physiology important to understand when setting up an assay [10][11][12][13]. Hamza then followed with the assay characteristics and criteria to take into consideration if the data generated should be used for interpretation of CYP3A4 activity and shared the recently published bioanalytical recommendations [13] on the development of a reliable assay, s uggesting that:…”
Section: Breakout Sessionsmentioning
confidence: 99%